Research On Partial Solar Eclipse 9 March 2016 Observed At Lapan Watukosek, Pasuruan - Setiahadi, Bambang; Risdianto, Dian Yudha (Universitas Muhammadiyah Surakarta, 2016)
The partial solar eclipse was observed during the eclipse event on 9 March 2016. Research was focused on mainly the intensity decreasing and increasing during contact of Moon-disk with Solar-disk. During first contact decreasing in intensity is in focused. After minimum intensity phase we further continue to inspect the intensity increasing. We posed that the intensity profile has some degree of asymmetry during complete solar eclipse process.